Amoeboid microglia in the periventricular white matter induce oligodendrocyte damage through expression of proinflammatory cytokines via MAP kinase signaling pathway in hypoxic neonatal rats - Kaur, C. (2011)
10.1111/j.1750-3639.2008.00138.x